Morphometric Study of Gall Bladder in Maharashtra Population (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Variations in morphology and metrical values of Gall Bladder (GB) is quite common. These variationsare frequently observed during imaging and procedures like laparoscopy and cholecystectomy. The anatomicalvariation of GB is essential to clinician.Method: 48 adult cadavers were studied to evaluate the morphometric study of GB. The size and shape wereclassified with percentage. The length and breadth were measured with tailors tape.Results: 52.08% pear shaped, 10.4% flask shaped, 12.5% cylinder shaped, 6.25% hour glass shaped, 6.25% intrahepatic, 2.08% left GB, 2.08% double GB were studied. The mean length of GB was 6.80 (±1.42), 2.82 (±0.78) wasmean breadth of GB, t test was 17.2 and p
Keywords: Morpho-metric, tailor tape, laparoscopy, cholecystectomy, Maharashtra